2020
DOI: 10.1097/dad.0000000000001460
|View full text |Cite
|
Sign up to set email alerts
|

Pretibial Pruritic Papular Dermatitis: A Comprehensive Clinical and Pathologic Review of Cases at a Single Institution

Abstract: Background: Studies characterizing clinical and pathologic details of pretibial pruritic papular dermatitis (PPPD) are scarce. Several cases of PPPD at our institution have displayed lymphocyte atypia and CD30 positivity, resembling lymphomatoid papulosis (LyP). We explore the clinical and histological spectrum of PPPD, with emphasis on lymphocyte atypia. Methods: Retrospective observational study of 40 archived pathological specimens (hematoxylin/eosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The latest comprehensive clinical and pathologic review focuses on lymphocyte atypia and CD30 expression in tissue biopsy to distinguish PPPD from lymphomatoid papulosis. The authors concluded that a relatively low number of atypical lymphocytes with weak or light CD30 staining intensity, as well as characteristic pruritus and pretibial distribution, favor PPPD over lymphomatoid papulosis (15).…”
Section: Discussionmentioning
confidence: 99%
“…The latest comprehensive clinical and pathologic review focuses on lymphocyte atypia and CD30 expression in tissue biopsy to distinguish PPPD from lymphomatoid papulosis. The authors concluded that a relatively low number of atypical lymphocytes with weak or light CD30 staining intensity, as well as characteristic pruritus and pretibial distribution, favor PPPD over lymphomatoid papulosis (15).…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 4 , 5 However, in 2019, Flores et al broadened the clinical and histological spectrum of PPPD in 38 patients, demonstrating its epidermal changes. 6 Lesions typically limit to unilateral or bilateral shins. Its prevalence is considered underestimated since the lack of disease recognition and misdiagnosis may occur.…”
Section: Discussionmentioning
confidence: 99%
“…Histological hallmarks of PPPD are the presence of superficial perivascular and interstitial lymphohistiocytic infiltration, epidermal changes of spongiosis and parakeratosis, and numerous stellate and multinucleated fibroblasts in the dermis. 1 , 2 , 6 The histological features that indicate persistent rubbing, consisting of uneven psoriasiform epidermal hyperplasia, marked compact orthokeratosis, hypergranulosis, and coarse bundles of collagen arranged in vertical streaks, are absent in PPPD, 1 , 2 , 6 and the lack of amyloid deposits in the dermis distinguishes PPPD from LA. 1 , 13 Despite unique PPPD histopathology, its pathogenesis has yet to be fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought to arise from chronic rubbing. PPPD was first reported in 2006, [3][4][5] and is likely an under-reported condition. As such, epidemiological data are limited.…”
Section: Questionmentioning
confidence: 99%
“…As such, epidemiological data are limited. Based on the two case series that are available (n=44+38=82), 3,4 the median age of onset is 50-60 years, with female dominance (1:3).…”
Section: Questionmentioning
confidence: 99%